PENGARUH PERKUATAN ANYAMAN BAMBU DENGAN VARIASI JARAK DASAR PONDASI KE LAPIS ANYAMAN DAN LEBAR ANYAMAN TERHADAP DAYA DUKUNG PONDASI MENERUS PADA TANAH PASIR POORLY GRADED - Muhammad Afief Ma'ruf (Universitas Lambung Mangkurat, 2014)
For a poorly graded sand that need a reinforcement held a loading test using a strip foundation model that gives the result of ultimate bearing capacity from the interaction diagram between the sand settlement and the value of bearing capacity, with the bearing capacity ratio (BCR) got from the comparison between the value of ultimate bearing capacity of reinforced sand and without reinforcement. From the test conclude that with the vary of space between bottom foundation to matt and with of matt also produce a vary of bearing capacity ratio. Keywords : Bearing Capacity Ratio, Strip Foundation, Bamboo Matt Reinforcement, Ultimate B.C.